PENGARUH MODAL, TENAGA KERJA TERHADAP PRODUKSI DAN PENDAPATAN INDUSTRI GARMEN DI KOTA DENPASAR - Yudistira, Nyoman Harry (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 10 (2022): vol.11.10. OKTOBER 2022 [3701 - 4009]DO - 10.24843/EEP.2022.v11.i10.p11, 2022)
The industrial sector has a very important role in national development, both large and small industries. Small industries such as the garment industry are able to contribute to the economy in Denpasar City. With the existence of small industries such as the garment industry, it will be able to increase regional income, especially Denpasar City and reduce unemployment. The purpose of the study was to analyze the direct influence of capital and labor on production in the garment industry in Denpasar City, to analyze the direct influence of capital, labor and production on income in the garment industry in Denpasar City, and to analyze the influence of capital and labor on income indirectly through production in the garment industry in Denpasar City. The population in this study is the garment industry in Denpasar City. The sample taken in this study was 86 respondents. The analysis techniques used are path analysis and sobel analysis. The results of this research analysis show that 1) Capital and labor have a positive and significant effect directly on production in the garment industry in Denpasar City; 2) Capital, labor and production have a positive and significant effect directly on income in the garment industry in Denpasar City; 3) Capital and labor have an indirect effect on income through the production of craftsmen in the garment industry in Denpasar City.